2013
DOI: 10.4049/jimmunol.1301348
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Phosphorylation of CD13 Regulates Inflammatory Cell–Cell Adhesion and Monocyte Trafficking

Abstract: CD13 is a large cell surface peptidase expressed on the monocytes and activated endothelial cells important for homing to and resolving the damaged tissue at sites of injury. We have previously shown that crosslinking of human monocytic CD13 with activating antibodies induces strong adhesion to endothelial cells in a tyrosine kinase- and microtubule-dependent manner. In the current study we examined the molecular mechanisms underlying these observations in vitro and in vivo. We found that crosslinking of CD13 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
108
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(112 citation statements)
references
References 59 publications
(71 reference statements)
4
108
0
Order By: Relevance
“…As an extracellular peptidase, CD13 cleaves single amino acid residues from small peptides, and therefore, its substrates vary depending on the tissue where it is expressed. However, our observations have clearly shown that CD13 is a surprisingly multifunctional molecule that often acts independently of its enzymatic activity to regulate diverse processes such as angiogenesis, inflammatory trafficking, Ag presentation, cell-cell adhesion, coronavirus infection, and maintenance of the stem cell niche (9)(10)(11)(12)(13)(14). Although it is difficult to reconcile how a single molecule can regulate such apparently disparate functions, the fact that CD13 participates in the endocytosis of various receptors may underlie its wide range of activities.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…As an extracellular peptidase, CD13 cleaves single amino acid residues from small peptides, and therefore, its substrates vary depending on the tissue where it is expressed. However, our observations have clearly shown that CD13 is a surprisingly multifunctional molecule that often acts independently of its enzymatic activity to regulate diverse processes such as angiogenesis, inflammatory trafficking, Ag presentation, cell-cell adhesion, coronavirus infection, and maintenance of the stem cell niche (9)(10)(11)(12)(13)(14). Although it is difficult to reconcile how a single molecule can regulate such apparently disparate functions, the fact that CD13 participates in the endocytosis of various receptors may underlie its wide range of activities.…”
Section: Discussionmentioning
confidence: 89%
“…We have identified CD13 as an inflammatory adhesion molecule that is required for optimal monocyte trafficking to sites of ischemic injury in numerous tissues (10,(12)(13)(14)21). In particular, in a model of ischemic peripheral muscle injury, the ratios of infiltrating monocytes in ischemic tissues from animals lacking CD13 were markedly altered, resulting in a distinctly "prohealing" cytokine milieu (13,14,22). However, healing of damaged tissue and muscle regeneration was unambiguously impaired in these mice despite the favorable inflammatory environment.…”
Section: Cd13 Regulates the Tlr4 Response To Damps Released In Ischemmentioning
confidence: 99%
See 1 more Smart Citation
“…In immune cells, IQGAP1 was found to be constitutively associated with CD13, a homing molecule and a cell surface peptidase expressed on monocytes and activated endothelial cells (Subramani et al , 2013). Further, CXCR2, a G-protein-coupled receptor (GPCR) involved in immune cell chemotaxis, directly binds IQGAP1 at the leading edge of human neutrophils (Neel et al , 2011).…”
Section: Iqgap1 and Cell Surface Receptors: A Puppeteer Extraordinairementioning
confidence: 99%
“…Monocyte markers PU.1/SPI1, MAFB, CSF1R, ANPEP, and M-CSF/CSF1 were expressed at comparable levels (Figure 3F) [66, 67]. The mature monocyte lineage marker CD14 was significantly up-regulated in the bone marrow of all equine CVID patients (FDR ≤ 0.033).…”
Section: Resultsmentioning
confidence: 99%